STRATEGI MADRASAH DALAM MEMBINA PRESTASI SANTRI PADA KOMPETISI SAINS MADRASAH (KSM) DI MAS DARUSSALAM SENGKUBANG - Syakirin, Syakirin; Hifza , Hifza; Sumar’in , Sumar’in (ILJ: Islamic Learning Journal, 2024)
The purpose of this study is to find out the madrasah strategy in improving students' achievement at MAS Darussalam Sengkurang. The research is a qualitative research with a descriptive approach, data collection methods with documentation, observation and interviews. Data analysis is descriptive. The results of the study state that the planning of madrasah strategic steps in fostering achievement is (a) Holding a strict selection of high-achieving students so that DSC participants really have the determination and strong desire to learn together, and are able to provide championships in the competition they achieve; (b) The existence of periodic evaluations, (c) Discipline in carrying out guidance (d) Planting religious values in the form of characterisation in the form of patience, sincere acceptance, not arrogant and always humble, especially humble nature. The madrasah programme to manage students' achievements is by making new innovations, namely forming special coaching in the form of DSC (Darussalam Science Club). After that, it is continued with routine guidance and participation in every competition held by any party which is useful for sharpening students.